DIGITALIZATION AND BRANDING OF WEST KLOMPANG VILLAGE, PAKONG DISTRICT, PAMEKASAN REGENCY IN THE DIGITAL ERA: DIGITALISASI DAN BRANDING DESA KLOMPANG BARAT KECAMATAN PAKONG KABUPATEN PAMEKASAN DI ERA DIGITAL - Izzulhaq, Mohammad; Fitri, Lailatul Hidayah; Pramudya, Nanda Hari; Fatihah, Nazilatul; Pramudita, Dwi Anggi; Putri, Ferdiana; Priyanto, Moh. Wahyudi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STAI Al Fithrah Surabaya, 2024)
The development of a village can be affected by the effective implementation of village digitalization. Village digitalization refers to efforts to develop digital infrastructure across sectors. Village digitalization has the potential to improve the village economy and make it easier to access information about the village. Therefore, we provide services that focus on developing digitalization and branding of West Klompang Village. Service begins on September 4-30 2023 using the observation, planning, implementation and evaluation approach. In this activity, it was seen that the people of West Klompang Village were very enthusiastic and actively participated. They participated with great enthusiasm. Village officials also appear to always be ready to help, provide proper facilities, and provide support to the West Klompang Village MBKM Internship Team. The Head of West Klompang Village was also actively involved in this outreach activity, providing full support. Apart from that, the potential in West Klompang Village looks very promising and worthy of further development. Apart from that, the results of the service include making a Bumdes logo, video documentation of the profile of West Klompang Village, and making labels for MSMEs. Collaboration is needed to increase community involvement in the creation of digitally connected villages. It is necessary to form a creative team to produce quality content, as well as provide training for village staff so they can innovate in the digital era.